A new poly(arylene oxide) with an extremely low dielectric constant as a fully aromatic hydrocarbon-type polymer. (10th December 2021) - Nakano, Akiyuki; Tanabe, Yoichi; Higashimura, Hideyuki
Abstract: A new aromatic polyether, poly(2-phenylphenylene oxide) with no CO structures was synthesized by regioselective oxidative polymerization of 2-phenylphenol with an artificial enzyme catalyst. The polymerization produced the C–O coupling polymer completely without CO structures, which occurred from oxygenation as well as C–C coupling with conventional catalysts. The polymer had a broad molecular weight distribution because of including bending and branching structures, although consisting mainly of linear units. After reprecipitation to increase the molecular weight, the resulting polymer showed not only high thermal stability exceeding 500 °C but also an extremely low dielectric constant of 2.22 @ 10 GHz as fully aromatic hydrocarbon-type polymers. Even without sp 3 -carbon nor fluorine atoms to reduce dielectric constants, the very low value would be caused by the asymmetrical 2-phenyl substituent in the repeating unit and the bending and branching structures in the polymer chain. Graphical abstract: Image 1 Highlights: A new poly(arylene oxide) was produced by a green synthetic method. Use of an artificial enzyme catalyst led to high selectivity for C–O coupling. The polymer expressed extremely low permittivity as an all-aromatic polyether. It is expected for insulating materials in the next 6G technology.